2017
DOI: 10.1016/j.devcel.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Proteomics Uncovers Ancient Associations of Cilia with Signaling Pathways

Abstract: Cilia are organelles specialized for movement and signaling. To infer when during evolution signaling pathways became associated with cilia, we characterized the proteomes of cilia from sea urchins, sea anemones, and choanoflagellates. We identified 437 high-confidence ciliary candidate proteins conserved in mammals and discovered that Hedgehog and G-protein-coupled receptor pathways were linked to cilia before the origin of bilateria and transient receptor potential (TRP) channels before the origin of animals… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 142 publications
3
102
2
Order By: Relevance
“…Apart from being a possible false negative, this discrepancy could be indicative of the diversity of ciliary components in eukaryotes (Nevers et al, 2017). A recent study using evolutionary proteomics has predicted MYCBPAP to be associated with cilia, and ISH of the FAM183A orthologue has shown to positively stain motile ciliated tissue in Xenopus laevis (Beckers et al, 2018, Sigg et al, 2017) . Additionally, EFCAB6 has previously been associated with sperm motility in human through proteomics (Amaral et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from being a possible false negative, this discrepancy could be indicative of the diversity of ciliary components in eukaryotes (Nevers et al, 2017). A recent study using evolutionary proteomics has predicted MYCBPAP to be associated with cilia, and ISH of the FAM183A orthologue has shown to positively stain motile ciliated tissue in Xenopus laevis (Beckers et al, 2018, Sigg et al, 2017) . Additionally, EFCAB6 has previously been associated with sperm motility in human through proteomics (Amaral et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have identified FAP57/WDR65 as a conserved component of motile cilia and flagella (Broadhead et al, 2006;McClintock et al, 2008;Arnaiz et al, 2010;Sigg et al, 2017;Blackburn et al, 2017), functional studies on fap57/wdr65 mutations are very limited. One report identified a missense mutation in WDR65 in a patient with Van der Woude syndrome, a cleft palate disorder, but this work did not establish a clear connection between the mutation and the cleft palate defects (Rorick et al, 2011).…”
Section: Function Of Fap57/wdr65 In Ciliary Motility In Other Speciesmentioning
confidence: 99%
“…Given the complexity of the microtubule-based 9+2 axonemal structure, motile ciliopathies are often under-diagnosed because of their genetic heterogeneity and multisystem variability (Werner et al, 2015). Yet many proteins of the ciliary axoneme are highly conserved (Li et al, 2004;Pazour et al, 2005;Albee et al, 2013), and so study of motile cilia in model organisms has provided insight into numerous genes and gene products potentially associated with PCD and other ciliopathies (Mitchison and Valente, 2017;Sigg et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It acts as a sensory antenna of these cells (Singla and Reiter, 2006;Satir et al, 2010;Anvarian et al, 2019) and is the basis of sensory organs, such as the vertebrate eye, and certain insect and invertebrate sensilla. It is closely related to motile 9+2 cilia, which are widely distributed from protists to man and also have sensory functions (Sigg et al, 2017). Mutations in ciliary proteins have been linked to human diseases including polycystic kidney disease (PKD) and primary ciliary dyskinesia (PCD), now collectively called ciliopathies (Fliegauf et al, 2007;Waters and Beales, 2011).…”
Section: Introductionmentioning
confidence: 99%